Characterization of Bordetella bronchiseptica associated with atrophic rhinitis outbreak in pigs - Shome, B R; Shome, Rajeswari; Mazumder, Y; Das, A; Rahman, M M; Kumar, A; Rahman, H; Bujarbaruah, K M (The Indian Journal of Animal Sciences, 2011)
The causes of mortality among pigs and piglets suffering from chronic respiratory disease with curvature of turbinate bone in an organized piggery in Meghalaya were investigated. Out of 50 pigs maintained at the farm. 24 (48.0%} were affected. Out of 9 postmortem samples and 12 nasal swabs from live pigs processed for bacterial isolation. II (52.3%) yielded the isolation of-B. brochiseptica. III vitro antibiotic sensitivity revealed more than 50% (6) isolates resistant to ampicillin, doxycycline, erythromycin, chloramphenicol, gentamycin and ciprofloxacin. In haemagglutination test, all the II B. brochiseptica isolates agglutinated rabbit RBC. The soluble proteins extracted frol116 isolates of B. bronchiseptica showed 23-27 major polypeptide bands within the molecular weight range of 114.0- 14.4kDa. Most of the immunogenic protein bands separated in western blot were in the range of 20-1 OOkDa. Plasmid analysis revealed 3 plasmid profiles and the number of plasmids varied from 1--4 with molecular size ranging from3.5--24.0kb. Dendogram analysis revealed similarity ranging fro111 more than 78-97% among the isolates. The restriction digestion of wild plusmids from B. brochiseptica with EcoRI suggested 3 recognition sites for 1 isolate and 2 sites for the other isolates. The present study established the involvement of B. bronchiseptica as causative agent in atrophic rhinitis in the pigs based on the isolation of the organisms and their characterization.